Estimation of acoustic impedance, its excess value and molar sound velocity of the binary mixture of 2-Butanol and m-Xylene for different compositions at different temperatures - Md. Sydur Rahman; Muhammad Habibullah (Universitas Islam Indonesia, 2020)
Measurements of physico-acoustic properties at ultrasonic level have been studied intensively for the binary mixture of 2-Butanol + m-Xylene system as a function of the composition at 298.15K to 323.15K by 5K intervals and at atmospheric pressure. Acoustic impedance(Z), excess acoustic impedance (ZE) and molar sound velocity (R) have been evaluated from the experimental values of speeds of sound and densities. The variation of these properties with composition and temperature suggests the presence of diopole-induced dipole interactions, hydrogen bond, induced electrostatic and dispersion forces. The observed negative values of ZE over the entire composition range of the system reinforce significant interactions between unlike molecules those dominate over other types. The variation of molar sound velocity (R) of the entire mixture suggests the rarefaction of the liquid mixture under study.